Representasi Nasionalisme pada Logo IKN NUSANTARA (Analisis Semiotika Charles Sanders Peirce) - Bagus Syahrudin, Dicky; Dahliah, Dahliah; Safitri, Riksa Diah Safitri (Program Studi Ilmu Komunikasi, 2024)
The Tree of Life logo, which is considered the origin of life, has three main components: roots, stems and flowers. The five roots at the bottom reflect the five principles of Pancasila. The seven sticks symbolize the large island chain in Indonesia. At its peak, there is a circle filled with 17 blooming flowers, symbolizing eternal freedom. The Tree of Life, apart from being a symbol of the source of life, also represents the abundant biological wealth in Indonesia. Seven stems growing from the roots, like flowing water, indicate that Indonesia is a maritime country, with seas and rivers as communication routes. All these elements are connected ina complete circle, where 17 blooming flowers develop which are an eternal symbol of freedom..This research focuses primarily on efforts to explore and gain a deeper understanding of how nationalism is represented in the Nusantara Capital City (IKN) logo. This research aims to identify and analyze the representation of nationalism contained in the IKN Nusantara logo. The research method used is qualitative with a descriptive approach. Data will be obtained through observation and document research. The collected data will be analyzed using various data analysis techniques, such as data reduction, data presentation, and data verification. This research will also use Charles Sanders Peirce's semiotic theory to analyze how nationalism is represented in the Nusantara Capital City (IKN) logo.